Prediction of the relaxation modulus of a fluoroelastomer using molecular dynamics simulation. (2nd November 2020) - Tamir, Erez; Srebnik, Simcha; Sidess, Arieh
Highlights: Prediction of thermomechanical properties of fluoropolymers from molecular model. Master curve from tensile relaxation modulus is compared with experiments. Onset of the glass transition is accurately predicted. Abstract: The tensile relaxation modulus of Viton A fluoroelastomers is calculated from the stress-strain response for different strain rates and temperatures using non-equilibrium molecular dynamics simulations. The calculated relaxation modulus is superimposed onto a master curve and compared with the experimentally measured relaxation modulus obtained using dynamical mechanical analysis. Comparison is also made with relaxation modulus calculated from equilibrium molecular dynamics simulation via the Green-Kubo relation and with analytical value of the glassy modulus calculated on the basis of a molecular lattice. Excellent correlation with experimental results is observed at times corresponding to the onset of the glass transition. The simulations capture β-relaxation that is compatible with Arrhenius theory at the onset of the glass transition and at the transition to α-relaxation. The proposed method is time efficient and in most cases more accurately reproduces the experimental behavior compared with the Green-Kubo relation.